2020
DOI: 10.1080/19490976.2020.1711685
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study reveals a microbiome signature that predicts the occurrence of post-operative enterocolitis in Hirschsprung disease (HSCR) patients

Abstract: Hirschsprung disease (HSCR) is a birth defect with an approximate incidence of 1/5,000 live births, and up to one-third of HSCR patients develop Hirschsprung-associated enterocolitis (HAEC), the leading cause of HSCR-related death. Very little is known about the pathogenesis, prevention, and early diagnosis of HAEC. Here, we used a prospective study to investigate the enteric microbiome composition at the time of surgery as a predictor for developing postoperative HAEC. We identified a microbiome signature con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 34 publications
4
37
1
Order By: Relevance
“…In this study, several gut microbiome derived metabolites and fermentation pathways, as a direct reflection of gut microbiome functionality, were established to be discriminating for the fecal metabolome of HD patients compared to their healthy siblings. Indeed, involvement of the gut microbiome in the pathogenesis of post-operative HD complications is in line with previously published reports 11 , 12 . This can be viewed as a consequence of the (partial) colon resection, as the latter drastically changes the intestinal microenvironment required for maintaining a healthy microbiome.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, several gut microbiome derived metabolites and fermentation pathways, as a direct reflection of gut microbiome functionality, were established to be discriminating for the fecal metabolome of HD patients compared to their healthy siblings. Indeed, involvement of the gut microbiome in the pathogenesis of post-operative HD complications is in line with previously published reports 11 , 12 . This can be viewed as a consequence of the (partial) colon resection, as the latter drastically changes the intestinal microenvironment required for maintaining a healthy microbiome.…”
Section: Discussionsupporting
confidence: 91%
“…To date, several studies have focused on the long-term post-surgical complications of HD and factors that might explain HAEC etiology and incidents. Increasing evidence points towards microbiome alterations as a cause or contributing factor in the development of enterocolitis in HD patients 11 , 12 . Moreover, a distinctly different gut microbial pattern has been demonstrated in HAEC patients, even after symptom remission, suggesting that enterocolitis may either be caused by or result in a disruption of the patient’s uniquely adapted intestinal microbiome 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Although direct evidence for a role of the immune system in the onset of HSCR is absent, RET and its pathway members are expressed by type 3 innate lymphoid cells (ILC3) and are involved in the organogenesis of intestinal Payer's patches [60,61]. Additionally, while it is clear that HSCR patients present with intestinal dysbiosis [62], further investigation would enlighten the paradoxical proposition of whether dysbiosis can contribute to HSCR, or if it is a consequence of impaired elimination mechanisms due to defective intestinal motility [63,64]. The role of microbes in HSCR pathogenesis is intriguing, yet not entirely surprising, since collective efforts have explored and divulged the important contribution of the gut microbiome in fine-tuning the ENS development and homeostasis [65][66][67][68][69][70][71][72], and vice versa [73].…”
Section: Enteric Neuropathiesmentioning
confidence: 99%
“…Several studies have reported that the microbial community extensively impacts host health by influencing intestinal epithelial cell proliferation, local and systemic immunity, and metabolism. Intestinal dysbacteriosis is associated with obesity, inflammatory bowel disease (IBD), nonalcoholic fatty liver disease, and metabolic syndrome [ 1 4 ]. Diet, environment, and host genetics influence the composition of the gut microbiota, and contribute to the high compositional diversity between individuals, which are comparable to unique fingerprints [ 5 8 ].…”
Section: Introductionmentioning
confidence: 99%